Viver na diferença… : a Casa Pia de Lisboa como espaço de inclusão - Ribeiro, Cláudia Pinto (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The dawning of the First Republic coincided with the creation of the spaces here revisited: institutes on the dependence of Casa Pia de Lisboa that gave shelter to all the boys who, due to their physical, moral and intellectual abnormality, were diminished to the condition of “embarrassment in the classroom, for their restlessness and retardation”. Being the casapian universe a laboratory of pedagogical modernity, is accentuated by its contribute to the inclusion of the abnormals in the society, confi gurating as an innovative institution of the pedagogical support to the abnormality in Portugal.